Answer:
B
Step-by-step explanation:
Answer:
5/4k^2
Step-by-step explanation:
P=5\dfrac{k}{6}\times \dfrac{3}{2k^3}.
We will be using the following property of exponents:
\dfrac{a^x}{a^y}=a^{x-y}.
We have
P\\\\\\=5\dfrac{k}{6}\times\dfrac{3}{2k^3}\\\\\\=\dfrac{5}{6}\times\dfrac{3}{2}k^{1-3}\\\\\\=\dfrac{5}{4}k^{-2}=\dfrac{5}{4k^2}.
Thus, the required product is \dfrac{5}{4k^2}.
Read more on Brainly.com - brainly.com/question/8858421#readmore
Answer:
x= 1
Step-by-step explanation:
x = 1 is the axis of symmetric for the graph
if we draw a line parallel to the y axis one units to the right side of the origin we get the line of symmetry of the graph.
and since the line of symmetry is parallel to y axis and passes thru the point (1, 0) it's equation is x= 1
The answer for the equation is 21